Beyond arrival: safeguarding unaccompanied asylum-seeking children in the UK. Issue 3 (21st June 2022) - Sanchez-Clemente, Nuria; Eisen, Sarah; Harkensee, Christian; Longley, Nicky; O'Grady, Rob; Ward, Allison
Abstract : Unaccompanied children (also called unaccompanied minors) are children who have been separated from both parents and other relatives and are not being cared for by an adult who, by law or custom, is responsible for doing so. From 2010 to 2020, unaccompanied minors accounted on average for 15.4% of the total number of first-time asylum applicants aged less than 18 years in the UK. These young people risk their lives and undergo traumatic journeys in search of a better life. However, when they arrive in the UK, they are vulnerable to significant ongoing traumatic experiences. In this review, we look at the reasons young people are forced to flee their countries, how they make their journey, and the risks and dangers they face along the way. We examine safety and victimisation risks faced by children and young people after arrival in the UK, which mechanisms and processes exist to safeguard these individuals, and examine the data available on outcomes of unaccompanied asylum-seeking child (UASC. Finally, we share two case examples that represent both the strengths and weaknesses of existing processes for UASC.